A Randomized Cohort Study: Is It Worth the Time to Receive Antiandrogenic Pretreatment Before Ovulation Induction for Women With Polycystic Ovary Syndrome? - Chen, Zhiyan; Tan, Jichun; Wang, Huichun; Zheng, Beihong; Liu, Jian; Hao, Guimin; Guo, Zaixin; Sun, Zhengyi; Yu, Qi (Frontiers in Endocrinology, 2022)
Objective To assess the effect of antiandrogenic pretreatment using combined oral contraceptives (COCs) and delayed ovulation induction in infertile patients with polycystic ovary syndrome (PCOS) with hyperandrogenism. Design Prospective, randomized open- labeled cohort study Setting Multicenter Patients PCOS patients with hyperandrogenism and requiring infertility treatments Interventions Randomization to direct ovulation induction of letrozole (letrozole group) or ethinylestradiol/cyproterone acetate (EE/CPA) for 3 months and subsequent letrozole-induced ovulation (EE/CPA+ letrozole group). The maximum number of ovulation induction cycle was three to four. Main Outcome Measures Ovulation rate, conception rate, ongoing pregnancy rate, and live birth rate were the main outcomes of the study. Results There were no significant differences in the cumulative ovulation, conception, ongoing pregnancy, and live birth rates between the letrozole and EE/CPA+ letrozole groups (cumulative ovulation: 206/254 [81.10%] vs. 169/205 [82.44%], risk ratio [RR]= 1.09 [0.68,1.76], P=0.713; conception: 44/90 [48.89%] vs. 42/76 [55.26%], RR= 1.29 [0.70,2.38], P=0.413; ongoing pregnancy: 33/90 [36.67%] vs. 33/76 [43.42%], RR=1.33 [0.71,2.47], P=0.376; and live birth: 32/90 [35.56%] vs. 31/76 [40.79%], RR=1.25 [0.67, 2.34], P=0.489). Conclusions The results of this study showed that COC pretreatment was not superior to direct letrozole-induced ovulation therapy in improving ovulation and pregnancy results in women with PCOS. There is no benefit to perform antiandrogenic therapy and delay ovulation induction in patients with PCOS in clinical practice.